Evaluation of health-related quality of life changes in an Australian rapid access chest pain clinic - J Andrew Black; James E. Sharman; Gang Chen; Andrew J. Palmer; Barbara de Graaff; Mark Nelson; Niamh Chapman; Julie A. Campbell (BMC Health Services Research)
Abstract Objective To evaluate the impact of absolute cardiovascular risk counselling on quality-of-life indices within a chest pain clinic. Data sources and study setting Primary data was collected at the Royal Hobart Hospital, Australia, between 2014 and 2020. Study design Patients attending an Australian chest pain clinic were randomised into a prospective, open-label, blinded-endpoint study over a minimum 12-months follow-up. Data collection / extraction methods The SF-36 questionnaire was completed at baseline/follow-up and SF-6D multi-attribute utility instrument’s health state utilities (HSU) were generated using SF-36 responses and the SF-6D’s Australian tariff. SF-6D minimal important difference was 0.04 points. Absolute cardiovascular risk was also stratified into high/intermediate/low-risk categories for exploratory analysis of summary HSUs and dimensional scores. ANZCTR registration number 12617000615381 (registered 28/4/17). Principal findings Of n = 189 patients enrolled, HSUs were generated for 96% at baseline (intervention n = 93, usual care n = 88) and 61% at follow-up. There were no statistical differences in age, sex, absolute cardiovascular risk or mean HSU between groups at baseline. Summary HSUs improved more for the intervention group and the median between-group difference exceeded the minimal important difference threshold (intervention 0.16 utility points, control 0.10 utility points). For Intervention patients with high absolute risk (≥ 15%), HSU did not significantly change. Conclusions Absolute cardiovascular risk counselling in a chest pain clinic yielded clinically meaningful improvement in health-related quality of life.